Analisi Komparasi Pengaruh Harga dan Kualitas Pelayanan Tehadap Kepuasan Pelanggan PT Lintas Trans Internasional dan PT Lintas Samudera Jaya - Puryanto, Galih; Maruta, IGN Anom; Nasution, Ute (Jurnal Dinamika Administrasi Bisnis, 2021)
ABSTRACTPrice and quality of service is a factor that is quite important to provide satisfaction to customers. Researchers try to in depth whether there is a difference in the price and quality of service in LTI Express and LSJ Express. The research method used is quantitative research with comparative research type. Comparative research is research used to compare two or more specific groups of variables. By using research instruments in the form of questionnaires. This study aims to find out the difference in price and quality of service to customer satisfaction at PT Lintas Trans Iinternasional and PT Lintas Samudera Jaya. The population in this study is all consumers who use LTI Express services and LSJ Express delivery services. The samples in this study were consumers in LTI Express and LSJ Express numbered 96 people divided into two groups namely LTI Express 46 respondents and LSJ Express 46 respondents. The results showed that there is no difference in price and quality of service to customer satisfaction in LTI Express and LSJ Express. In variable prices get insignificant results so there is no difference. In variable quality of service obtained insignificant results so there is no difference. On variable customer satisfaction get insignificant results so there is no difference between LTI Express and LSJ Express on customer satisfaction variables.Keywords: Price, Quality of Service, Customer Satisfaction